Role of procalcitonin in early diagnosis of neonatal sepsis - Hasan, Fareedul; Khan, Shamshad A.; M. K., Maharoof; Muhammed, Niyaz (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal sepsis is the most common cause for neonatal mortality and morbidity in India, Therefore it is essential that we diagnose early onset sepsis using clinical signs and symptoms and rapid diagnostic techniques and start appropriate treatment without any delay. Various diagnostic tests that differentiate infected and non-infected neonates particularly in the first few days of life can potentially make significant impact on the neonatal care. Methods: This was a hospital based clinical prospective study, done in the NICU department of pediatrics at Yenepoya medical college hospital, from January 2013 to December 2013. Sample size in this study was 50. All consecutive neonates fulfilling the inclusion and exclusion criteria were subjected to investigations like serum Procalcitonin, CRP, Total count, Gastric aspirate, Peripheral smear and Blood culture before starting treatment with antibiotics. Positive blood culture was taken as proven sepsis. The results obtained from our study parameters were statistically compared with cases of proven sepsis. Results: In our study 16(32%) out of 50 neonates had proven sepsis. In comparison to the other markers of neonatal sepsis Elevated levels of serum Procalcitonin was found to be the most sensitive test with sensitivity of 100%, specificity of 50%, positive predictive value of 48.5%and negative predictive value of 100% and with a very highly significant p value of <0.001.Among the levels of PCT moderately elevated (2-10ng/dl) had sensitivity of 100%, specificity of 84.5%, PPV of 62.5% and NPV of 100% and highly elevated (>10ng/dl) had sensitivity of 100%, specificity of 80%, PPV of 75% and NPV of 100%. Conclusions: The use of procalcitonin in the diagnosis of neonatal sepsis has proved to be very useful compared to other regular sepsis markers. Procalcitonin performs better than CRP in the diagnosis of neonatal infection. Serum Procalcitonin levels >2 ng/dl has got a better sensitivity; PPV and NPV thus help us not only in the early diagnosis and also in the prognosis of the treatment and helps us in guiding in reducing the unwanted usage on antibiotics.